Intestinal parasites in pigs confined in a creation in the municipality of Pinheiral - RJ - Carreiro, Caroline C.; Coelho, Cleide Domingues; Jorge, Jorge Luis B. Pereira; Costa, Nelson Oscaranha Gonsales; Paiva, Rafael do Valle; Filho, Walter Leira Teixeira; da Rosa, Adriane Garcia; de Jesus, Vera Lúcia T. (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Carreiro C.C., Coelho C.D., Jorge J.L.B.P., Costa N.O.G., Paiva R.V., Teixeira Filho W.L., Rosa A.G. & de Jesus V.L.T. [Intestinal parasites in pigs confined in a creation in the municipality of Pinheiral - RJ.] Parasitos intestinais em suínos confinados em uma criação no município de Pinheiral- RJ. Revista Brasileira de Medicina Veterinária, 38(Supl.2):117-122, 2016. Programa de Pós-Graduação em Medicina Veterinária, Instituto de Veterinária, BR 465 Km 7, Campus Seropé- dica, RJ 23897-970, Brasil. E-mail: carolinecarreiro@yahoo.com.br Gastrointestinal disorders are frequently observed in pigs in different age groups. It is responsible for important economic losses, not only the mortality rate of piglets, as the reduction of weight gain and medical expenses. Moreover, in sows it is associated with reduced fertility and irregular repetitions of heat. Despite the great development of intensive pig farming, little is known about the occurrence of endoparasites in this species. Considering that enteritis cause serious economic losses, the objective of this study was to identify the main parasites in stool confined sows and piglets. Fifty-five fecal samples (23 sows and 32 piglets) were subjected to the examination of fresh and centrifugal technique - fluctuation in sugar, and observation by optical microscopy. The results showed that 72.7% of the animals were positive for at least one parasite, being quite significant co-infection, where 75% of infected animals had more than one agent. In matrices, coccidia presented more frequent (60.87%), followed by Parabasalidea (52.17%), Strongyloidea (47.8%) and Balantidium (26.08%). Coccidia are also more common in piglets (25%), followed by Strongyloidea (18.75%), Balantidium (12.4%) and parabasalideo (9.37%). Thus, we can conclude that despite the great development of intensive pig farming, the intestinal parasites are a major obstacle in the production, with the need for more effective programs of prevention and control.